Morphofunctional Alterations in Endocrine Pancreas of Short- and Long-term Dexamethasone-treated Rats - Rafacho, A. [UNESP]; Abrantes, J. L. F.; Ribeiro, D. L. [UNESP]; Paula, F. M.; Pinto, M. E. [UNESP]; Boschero, A. C.; Bosqueiro, José Roberto [UNESP] (Georg Thieme Verlag Kg, 2011)
Long-term dexamethasone therapy may induce peripheral insulin resistance (IR), which in turn elicits increased beta-cell function and proliferation. However, whether such adaptive compensations occur during short-term treatment with dexamethasone is unclear. Here, we compared morphofunctional parameters in endocrine pancreas after short- and long-term dexamethasone administration. Groups of rats received daily i.p. injection of 1 mg/kg b.w. dexamethasone for 1 (DEX-1), 3 (DEX-3), or 5 consecutive days (DEX-5), whilst control rats were saline-treated (CTL). Despite the absence of apparent IR in DEX-1 rats, this group exhibited increased circulating insulin levels and glucose-stimulated insulin secretion (GSIS), compared to the CTL group (p < 0.05). Evident IR as well as marked hyperinsulinemia and GSIS, as judged by the static and dynamic insulin secretion values, were observed in DEX-3 and DEX-5 rats (p < 0.05). GSIS in islets cultured with 1 mu M dexamethasone was lower compared to the control (p < 0.05). Marked increases in beta-cell proliferation were observed in DEX-3 and DEX-5 rats, compared to CTL and DEX-1 rats (p < 0.05). The alterations observed in DEX-3 rats were more pronounced in DEX-5 rats, which also exhibited a higher content of islet Cdk4 and Cd2 proteins, compared to the CTL group (p < 0.05). We conclude that short-term dexamethasone treatment (DEX-1) induces an increase in beta-cell function that does not require the presence of discernible IR. As the treatment continues, the IR develops rapidly, and increased insulin secretion as well as beta-cell hyperplasia is demanded for the appropriate maintenance of glucose homeostasis.
Keywords: beta-cell proliferation; dexamethasone; Glucocorticoid; insulin secretion; insulin resistance; short- and long-term treatment